China’s Wonderland: An Analysis on Chinese Theme Parks’ Cultural Plight - ZHANG, Qiuyi (2010)
Tourism is a relatively new research field in China. Theme parks, being a branch of tourism industry, were firstly introduced to Chinese people two decades ago. However, the current situation and issues of Chinese theme parks has not been well studied. This research intended to explore the relationship between Chinese culture and theme parks as well as problems of the existing Chinese theme parks. Tourist behaviour, tourism market segmentation, culture transmission theory and Hofstede’s culture theory were applied in the research. Twenty-one semi-structured in-depth interviews and two focus groups were pursued for data collection. Based on the data analysis, two main findings were identified: the segmentation of Chinese theme parks is rather crude; and the themes lack originality and uniqueness.